Journey on VX-809-Based Hybrid Derivatives towards Drug-like F508del-CFTR Correctors: From Molecular Modeling to Chemical Synthesis and Biological Assays - Alice Parodi; Giada Righetti; Emanuela Pesce; Annalisa Salis; Valeria Tomati; Cristina Pastorino; Bruno Tasso; Mirko Benvenuti; Gianluca Damonte; Nicoletta Pedemonte; Elena Cichero; Enrico Millo (MDPI AG, 2022)
Cystic fibrosis (CF) is a genetic disease affecting the lungs and pancreas and causing progressive damage. CF is caused by mutations abolishing the function of CFTR, a protein whose role is chloride's mobilization in the epithelial cells of various organs. Recently a therapy focused on small molecules has been chosen as a main approach to contrast CF, designing and synthesizing compounds acting as misfolding (correctors) or defective channel gating (potentiators). Multi-drug therapies have been tested with different combinations of the two series of compounds. Previously, we designed and characterized two series of correctors, namely, hybrids, which were conceived including the aminoarylthiazole (AAT) core, merged with the benzodioxole carboxamide moiety featured by VX-809. In this paper, we herein proceeded with molecular modeling studies guiding the design of a new third series of hybrids, featuring structural variations at the thiazole moiety and modifications on position 4. These derivatives were tested in different assays including a YFP functional assay on models F508del-CFTR CFBE41o-cells, alone and in combination with VX-445, and by using electrophysiological techniques on human primary bronchial epithelia to demonstrate their F508del-CFTR corrector ability. This study is aimed (i) at identifying three molecules (9b, 9g, and 9j), useful as novel CFTR correctors with a good efficacy in rescuing the defect of F508del-CFTR; and (ii) at providing useful information to complete the structure-activity study within all the three series of hybrids as possible CFTR correctors, supporting the development of pharmacophore modelling studies, taking into account all the three series of hybrids. Finally, in silico evaluation of the hybrids pharmacokinetic (PK) properties contributed to highlight hybrid developability as drug-like correctors.